Analysis Of The Dynamics Of The Prevalence And Incidence Of Mental Disorders And Behavior As A Result Of The Use Of Psychoactive Substances In Ukraine For The Period 1990–2014 Years - Markozova, Lubov; Linskiy, Igor; Baranenko, Oleksiy (Psychiatry, Neurology and Medical Psychology, 2017)
The analysis outlined the dynamics of the prevalence and incidence of mental disorders and behavior (MDB) as a result of the use of psychoactive substances (PS) in Ukraine during 1990-2014 years. The paper found out that the relative amount of acute and chronic disorders due to use of surfactants in comparison with other mental disorders for the past five years has remained almost unchanged; the incidence of alcohol dependence declined in 2014 by almost 2-fold compared to 2008. Dynamics of disease of alcohol addiction and other surfactants has opposite nature: some increase in the incidence of alcohol dependence is accompanied by a decrease in the incidence of other surfactants. Regional distribution of MDB morbidity is due to the use of alcohol in a mosaic pattern with approximately equal representation in predominantly agricultural areas of the north and west, and in the industrial areas of the east and south of the country. The abundance of drug substance abuse in 2014 has a clear zoning.